TEO-PEDAGOGI PERKAWINAN HINDU DI BALI - Wardana, Kadek Agus; Sukrawati, Ni Made; Putri, Ni Kadek Ayu Kristini (Universitas Tabanan, 2023)
Marriage Ceremony is a marriage vow binding ceremony carried out by men and women with the intention of formalizing the marriage bond with the aim of forming a harmonious household or family. Godly education is very closely related to a marriage ceremony in Balinese Hindus in every process with the aim of glorifying their offspring as a suputra. To produce valid and reliable data, this paper uses a qualitative writing style. In producing logical data, this paper performs several stages of data sorting in the form of: 1). Data reduction, 2). Display data, 3). Verifying data, and 4). Interpreting research data. In its presentation, measurable analysis becomes the basis for processing the data obtained. The perfection of this paper cannot be separated from the library technique which is carried out through an assessment of the existing literature on Google Scholar. Changes in the era of globalization towards modern, there is a lot of deconstruction of a marriage. Starting from ceremonies that are hedonism to jor rods with prestige so that ordinary people who lack knowledge of traditions become reluctant and afraid of a tradition such as pre-weddings that cost tens of millions, lavish receptions held in classy places to modifications to magnificent decorations. These understandings are very rarely disseminated to the general public, even though the constructive aspect of a marriage is apart from continuing the new regeneration in Hinduism, it is to atone for the sins of the previous ancestors.